2013
DOI: 10.1017/s104161021300121x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic covariates of chronic opioid and non-opioid analgesic use in rural-dwelling older adults: the MoVIES project

Abstract: Background To describe covariates and patterns of late-life analgesic use in the rural, population-based MoVIES cohort from 1989 to 2002. Methods Secondary analysis of epidemiologic survey of elderly people conducted over six biennial assessment waves. Potential covariates of analgesic use included age, gender, depression, sleep, arthritis, smoking, alcohol, and general health status. Of the original cohort of 1,681, this sample comprised 1,109 individuals with complete data on all assessments. Using traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In chronic pain patients, it has been estimated that 21% to 29% misuse opioids-meaning these medications are used contrary to the prescription-while 8% to 12% are addicted to opioids-meaning there is a pattern of continued use despite a demonstrated potential for harm [18]. Opioid use in our database is higher than in a 2007 California sample [19], and a nationally-representative sample from 2013 [20], but lower than reported in a 2008 sample from Utah [15], a national sample of Medicare patients with fragility fracture [7], a 2002 rural sample of elderly people in Pennsylvania [20], and a meta-analysis of patients with chronic pain [18].…”
Section: Discussionmentioning
confidence: 79%
“…In chronic pain patients, it has been estimated that 21% to 29% misuse opioids-meaning these medications are used contrary to the prescription-while 8% to 12% are addicted to opioids-meaning there is a pattern of continued use despite a demonstrated potential for harm [18]. Opioid use in our database is higher than in a 2007 California sample [19], and a nationally-representative sample from 2013 [20], but lower than reported in a 2008 sample from Utah [15], a national sample of Medicare patients with fragility fracture [7], a 2002 rural sample of elderly people in Pennsylvania [20], and a meta-analysis of patients with chronic pain [18].…”
Section: Discussionmentioning
confidence: 79%
“…68 A recent study using data from the National Ambulatory Medical Care Survey showed that from 1999–2000 to 2009–2010, the percentage of clinic visits for older patients where an opioid was prescribed rose from 4.1% to 9.0%. 9 Most commonly, hydrocodone was used in combination with acetaminophen or ibuprofen.…”
Section: Epidemiology Of Opioid Use and Benefits For Cncp In The Ementioning
confidence: 99%
“…19,22 Indeed, pharmacodynamic sensitivity helps explain risks of opioids unique to geriatric patients. 6,8,19,29,31 In a meta-analysis of pooled data from 6 observational studies, older adults exposed to opioids had a 38% increased likelihood of fractures (relative risk [RR] 1.38; 95% confidence intervals [CI] 1.15–1.66). 32 Moreover, timing of opioid initiation may be an important consideration.…”
Section: Age-related Pharmacokinetic and Pharmacodynamic Changes And Rmentioning
confidence: 99%
“…Long-term opioid use appears to be increasing over time, and older women may be vulnerable to using these medications for longer than recommended (Campbell et al, 2010). But evidence for increasing risk with age is mixed as individuals move into the oldest age-groups, such as those aged 75 and over (Han, Kass, Wilsey, & Li, 2013; Karp et al, 2013). Older adults with cognitive problems are at risk of taking inappropriate medications that can further impact their cognition (Weston, Weinstein, Barton, & Yaffe, 2010).…”
Section: Risk Factors For Alcohol and Drug Problemsmentioning
confidence: 99%